Rebranding Artisan Batik for Gen Z Women: A Social Media Visual Communication Strategy for Bhumi Khayuna - Karenina Santikaputri; Ira Wirasari; Fajar Ciptandi (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: The artisan fashion industry faces challenges in renewing its audience, particularly in reaching Generation Z women with strong digital preferences and environmental awareness. Bhumi Khayuna, a sub-brand of Jarit, experiences identity ambiguity and limited visual differentiation, reducing the effectiveness of its marketing and rebranding efforts on social media. Objective: This study aims to develop a rebranding strategy for Bhumi Khayuna to strengthen brand identity, enhance engagement, and connect with Generation Z female consumers through relevant digital communication. Methods: This qualitative study employed five stages: identifying brand problems, analyzing internal brand elements, evaluating competitors and audience preferences through surveys and social media observations, developing visual communication strategies, and validating the proposed rebranding strategy. Data were analyzed through triangulation of interviews, observations, and competitor content analysis. Results: The findings indicate that Bhumi Khayuna requires an independent visual identity, differentiated communication strategies, and social media content integrating sustainability narratives, modern aesthetics, and community engagement. Generation Z consumers show interest in functional products, ethical production, transparency, and interactive brand experiences. The integration of clear brand architecture, AIDA-based copywriting, earth-tone visuals, and sustainability storytelling achieved a 72% preference among respondents. Conclusion: This study provides practical guidance for artisan fashion brands in developing authentic and audience-oriented rebranding strategies while contributing to research on branding, visual communication, and Generation Z consumer behavior in the digital era.